The Anthology of American Folk Music and Working-Class Music - Rosenberg, Neil V. (Labour / Le Travail, 1998)
The article reviews and comments extensively on the iconic recording, "The Anthology of American Folk Music and Working-Class Music," reissued with additional notes by Smithsonian Folkways in 1997. The original recordings were made by Harry Smith between 1927 and 1932; the anthology was first assembled and issued in 1952 by Ralph Rinzler. The author concludes that while the collection is an amazing and insightful document of its time, it is also representative of a particular American cultural and political mythology. The conclusion also briefly discusses why there is no comparable Canadian anthology.